Atuação internacional dos municípios brasileiros à luz da constituição dirigente de 1988: um estudo de caso da Secretaria Municipal de Relações Internacionais e Federativas de São Paulo - Simini, Danilo Garnica [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In parallel to the urbanization process that begins in the 1950s in the country and extends to the present day, there is a process of increasing recognition of municipalities as federal entities, from the formal assignment of new skills, which makes them important agents public policy inductors, and give them autonomy in the political, administrative and financial. And the Federal Constitution of 1988 should be considered innovative document in this regard. It turns out that the assumption of new responsibilities by the municipalities was not accompanied by sufficient resources so that they satisfactorily heeding the public demands. Thus, this new panorama caused the cities to seek new ways to meet their demands, emerging as alternative to international operations. In Brazil this international action takes place in several ways, including the organization of Municipal Departments of International Relations. But historically it fell to the Union the monopoly of international activity, resulting in principle legal obstacles to this action, tradition maintained even in the Constitution of 1988. However, understanding the Constitution should not be made starting from the assumption that the 1988 Constitution sets up a mere instrument defining skills (Constitution warranty), but rather a political-legal document defining the purpose and future action programs in order to improve social and economic conditions of the population (Constitution Manager). In this sense, all public action should be to the north the objectives of the Federative Republic of Brazil listed specifically in Article 3 of the current Constitution. The proposed research aims to investigate, from a ruling establishment reading if there is compatibility between the international operations of Brazilian municipalities through the Municipal Departments of International Relations and the Constitution interpreted in this way, specifically...

Paralelamente ao processo de urbanização que se inicia nos anos de 1950 no país e se estende até os dias atuais, ocorre um processo de aumento do reconhecimento dos municípios enquanto entes federados, a partir da atribuição formal de novas competências, o que os torna importantes agentes indutores de políticas públicas, além de conferir-lhes autonomia na área política, administrativa e financeira. E a Constituição Federal de 1988 deve ser considerada documento inovador neste aspecto. Ocorre que a assunção de novas responsabilidades pelos municípios não foi acompanhada de recursos suficientes para que estes atendessem de modo satisfatório às demandas públicas. Assim, este novo panorama fez com que as cidades buscassem novas formas de atender suas demandas, surgindo como alternativa a atuação internacional. No Brasil esta atuação internacional se dá de diversas formas, entre elas, a organização de Secretarias Municipais de Relações Internacionais. Porém, historicamente sempre coube à União o monopólio da atividade internacional, ocasionando, em princípio, obstáculos jurídicos a esta atuação, tradição mantida mesmo na Constituição Federal de 1988. Todavia, a compreensão do texto constitucional não deve ser feita partindo-se do pressuposto de que a Carta de 1988 configura um mero instrumento definidor de competências (Constituição Garantia), mas sim um documento político-jurídico definidor de fins e programas de ação futura no sentido de melhorias das condições sociais e econômicas da população (Constituição Dirigente). Nesse sentido, toda atuação pública deve ter por norte os objetivos da República Federativa do Brasil elencados especialmente no artigo 3º do texto constitucional vigente. A pesquisa proposta visa investigar, a partir de uma leitura da Constituição Dirigente se há, compatibilidade entre a atuação internacional dos municípios...
Keywords: Direito constitucional; Políticas públicas; Constitucionalismo; Brasil - Constituição; São Paulo (Estado) - Municípios